2011
DOI: 10.1111/j.1745-4514.2011.00590.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibition and Differentiating Effects of Protein Hydrolysates From Bovine Colostrums on Human Leukemic U937 Cells

Abstract: This research investigates the effects of bovine colostrums and their protein hydrolysates on human mononuclear cell (MNC) growth, on the secretion of cytokines (interleukin‐1β, interferon‐γ and tumor necrosis factor‐α) as well as nitric oxide, and on the growth inhibition of human leukemic U937 cells. The results indicate that the colostrum hydrolysates obtained by porcine small‐intestinal enzymes (PIS) exhibit more significant inhibitory effect on U937 cell growth than do the caseins (PIC) and the whey (PIW)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Bovine colostrum is the first milk produced postpartum and is typically defined as the first six postpartum milkings collected during the period of transition from colostrums to milk [ 1 , 2 ]. Several researchers have compared the composition of colostrums with those of mature milk and concluded that colostrums have higher levels of protein, lower levels of fat, a lactose solution rich in immunoglobulins, and other important immune elements and mediators [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bovine colostrum is the first milk produced postpartum and is typically defined as the first six postpartum milkings collected during the period of transition from colostrums to milk [ 1 , 2 ]. Several researchers have compared the composition of colostrums with those of mature milk and concluded that colostrums have higher levels of protein, lower levels of fat, a lactose solution rich in immunoglobulins, and other important immune elements and mediators [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The minor constituents include immunoglobulins (9%), bovine serum albumin (5.5%), lactoferrin, phospholipoproteins, bioactive factors, and enzymes [ 7 ]. Several functional and biological activities of bovine colostrum whey protein and whey protein hydrolysates have been reported, such as U937 cell growth inhibition and immunomodulatory activities [ 1 ], antioxidation activities [ 8 ], inhibition of angiotensin I-converting enzyme and downregulation of fatty acid synthesis in liver [ 7 ], and inhibition of DNA oxidative damage and LDL oxidation [ 2 ]. Protein hydrolysate is a mixture of proteoses, peptones, peptides, and free amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…Bovine colostrums is the first milk produced postpartum and is typically defined as the first six postpartum milking collected during the period of transition from colostrums to milk [7,8]. Several researchers have compared the composition of colostrums with those of mature milk and concluded that colostrums have higher levels of protein, lower levels of fat, a lactose solution rich in immunoglobulins, and other important immune elements and mediators [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…A suspension of 5 × 10 5 cells/mL in an RPMI 1640 medium was prepared. MTT (3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide) assays for determining the growth of MNCs were modified from those of Liao et al [ 26 ] and Chen et al [ 27 ]. MNCs were incubated with various concentrations of different T. triangulare extracts in medium, medium only, and medium with same extract volume of phosphate buffer saline (PBS; control) at 37°C in a humidified atmosphere containing 5% CO 2 for 24 and 72 hours, respectively.…”
Section: Methodsmentioning
confidence: 99%